2013
DOI: 10.2337/db12-1380
|View full text |Cite
|
Sign up to set email alerts
|

Munc18b Is a Major Mediator of Insulin Exocytosis in Rat Pancreatic β-Cells

Abstract: Sec1/Munc18 proteins facilitate the formation of trans-SNARE (soluble N-ethylmaleimide–sensitive factor attachment protein receptor) complexes that mediate fusion of secretory granule (SG) with plasma membrane (PM). The capacity of pancreatic β-cells to exocytose insulin becomes compromised in diabetes. β-Cells express three Munc18 isoforms of which the role of Munc18b is unknown. We found that Munc18b depletion in rat islets disabled SNARE complex formation formed by syntaxin (Syn)-2 and Syn-3. Two-photon ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 36 publications
4
79
1
1
Order By: Relevance
“…Remarkably, these newcomer SGs are recruited to the PM to undergo exocytosis with minimal to no residence time on the PM [4,5]. We had identified the exocytotic machinery mediating newcomer SGs [10,[16][17][18][19]]-a second SM-SNARE complex comprised of Munc18b, Syn-3, VAMP8 and SNAP25. In that body of work, we showed that depletion of endogenous Syn-3 [10] or VAMP8 [17] reduced newcomer SGs and that when exogenously expressed they restored the deficient newcomer SGs without affecting pre-docked SGs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Remarkably, these newcomer SGs are recruited to the PM to undergo exocytosis with minimal to no residence time on the PM [4,5]. We had identified the exocytotic machinery mediating newcomer SGs [10,[16][17][18][19]]-a second SM-SNARE complex comprised of Munc18b, Syn-3, VAMP8 and SNAP25. In that body of work, we showed that depletion of endogenous Syn-3 [10] or VAMP8 [17] reduced newcomer SGs and that when exogenously expressed they restored the deficient newcomer SGs without affecting pre-docked SGs.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that pancreatic acini employed Munc18c-Syn-4-VAMP8-SNAP23 as the putative SM-SNARE complex mediating basolateral exocytosis that causes pancreatitis [25][26][27]. We showed that all beta cell Syns displayed promiscuous binding to VAMP2 and VAMP8 and to SNAP25 and SNAP23, although each Syn has a preference for a particular VAMP [16,17]. To determine whether beta cell Syn-4-Munc18c complexes bind to VAMPs and SNAP25 isoform SNAP23, we performed immunoprecipitation experiments in INS-1 cells (Fig.…”
Section: Syn-4 Depletion Diminishes Biphasic Gsis By Reducing Exocytomentioning
confidence: 99%
See 2 more Smart Citations
“…Munc18b is one of the Munc18 isoforms that is expressed in pancreatic islets, and the deletion of Munc18b by shRNA reduced insulin secretion. 37) Interestingly, a Munc18b mutant, Munc18b-K314L/R315L (Munc18b-KR), is a mutant that facilitates SNARE complex assembly. The laboratory of Lam and Gaisano showed that Munc18b-KR facilitated the complex formation between Syntaxin1/2-VAMP2-SNAP25 and Syntaxin3-VAMP8-SNAP25 in islets that were stimulated by glucose, GLP-1, and IBMX.…”
Section: Mode Of Exocytosismentioning
confidence: 99%